(untitled) (Journal of Bangladesh Academy of Sciences, 2014)
A ferrocenyl imine complex, Fc-C(CH3)=N-NH-C6H3-2,4-(NO2)2 (Fc = ferrocenyl) has been synthesized by the condensation reaction between acetylferrocene and 2,4-dinitrophenyl hydrazine. The compound was synthesised previously, and characterized by IR, 1H and elemental analysis. It was further characterized by 13C 1H NMR spectroscopy and mass spectrometry. The redox property of the complex was studied by cyclic voltammetry, differential pulse voltammetry and chronocoulometry. The redox process of the complex was found to be reversible at a platinum-disc electrode, and the redox potential of the imine complex was shifted to more anodic position with respect to ferrocene. The redox reactivity of the complex was enhanced in the presence of oxygen. DOI: http://dx.doi.org/10.3329/jbas.v38i2.21342 Journal of Bangladesh Academy of Sciences, Vol. 38, No. 2, 177-187, 2014